Sabah's unrelenting exclusionary and inclusionary politics - Somiah, Vilashini (Nanyang Technological University, 2021)
Sabah's political and socio-economic issues are linked to the state's long and contentious history of migration. Many of these problems arose in the 2020 Sabah state election, which was underscored by anti-immigrant sentiments. Underlying all of these is the politics of identity of the Sabahans. Indigenous Sabahans such as the Kadazandusuns tend to separate themselves from the Malay-Muslim majority of Malaysia. This is compounded by the identities of Sabah's migrant population, which remains largely “foreign” in the eyes of indigenous communities. Often, both federal and state governments disregard these issues, leading to policies that alienate the inhabitants of Sabah. This paper unpacks the issues involved and lays out the interconnected political, security, and socio-economic concerns related to the governing of Sabah and the state’s relationship with the federal government. The paper examines the treatment of indigenous Sabahans and migrants, and why it is important to identify the challenges for the future socio-economic development and stability of Sabah.